The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.2147/sccaa.s204099
|View full text |Cite
|
Sign up to set email alerts
|

<p>Stem-cell therapy for ovariectomy-induced osteoporosis in rats: a comparison of three treatment modalities</p>

Abstract: Background: Recent studies have shown that ovariectomy-induced osteoporosis in rats can be reversed by infusion of osteoblasts cultured from mesenchymal stem cells (MSCs). This study compares the influence of MSCs, osteoblasts, and exosomes derived from osteoblasts for the treatment of osteoporosis. Methods: Osteoporosis was induced in 40 female Sprague Dawley rats by performing ovariectomy. After 12 weeks, bone marrow was harvested and MSCs separated from bone-marrow aspirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Between the new approaches intended to solve this medical necessity cellular therapy emerge as one that may have large application [50][51][52][53][54][55][56][57][58]. The DDD is a problematic scenario for tissue regeneration due to the harsh microenvironment that resident cells are immersed [54,56].…”
Section: Several Clinical Reports and Clinical Trials Have Provedmentioning
confidence: 99%
See 3 more Smart Citations
“…Between the new approaches intended to solve this medical necessity cellular therapy emerge as one that may have large application [50][51][52][53][54][55][56][57][58]. The DDD is a problematic scenario for tissue regeneration due to the harsh microenvironment that resident cells are immersed [54,56].…”
Section: Several Clinical Reports and Clinical Trials Have Provedmentioning
confidence: 99%
“…It is very important to when they were used to treat early stages of disc degeneration [56,58]. There was also reported that tissue specifi c progenitor cells seem to be more effective than MSC [56][57][58].…”
Section: Several Clinical Reports and Clinical Trials Have Provedmentioning
confidence: 99%
See 2 more Smart Citations
“…Stem cell transplantation is proposed as a potential treatment strategy for patients with osteoporosis [8]. Some experimental studies have been conducted in animal models of osteoporosis to evaluate the therapeutic effect of stem cell transplantation [8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Stem cells used in animal models of osteoporosis include bone marrow mesenchymal stem cells (BMSCs) [21], adipose-derived stem cells (ADSCs) [16], amniotic membrane mesenchymal stem cells (AM-MSCs) [12], and human umbilical cord blood-derived mesenchymal stem cells (hUCB-MSCs) [20].…”
Section: Introductionmentioning
confidence: 99%